The High Potential of Ozone Gas to Inactivate Echinococcus granulosus Protoscoleces During Hydatid Cyst Surgery - Mahmoudvand, Hossein; Harandi, Majid F.; Niazi, Massumeh; Rouientan, Abdolreza; Mohammadi-Moghadam, Fazel; Dezaki, Ebrahim Saedi (Infectious Disorders - Drug Targets, 2020)
Background: In medicine, ozone therapy is effectively used in a broad spectrum of diseases. Reviews have shown that ozone gas demonstrates potent antimicrobial effects against a wide range of pathogenic microorganisms, such as oral bacteria, fungi, viruses, and parasite even in resistant strains. The present investigation was designed to assess the protoscolicidal effects of ozone gas on hydatid cysts protoscoleces in vitro and in vivo. Methods: Hydatid cyst protoscoleces were acquired from sheep livers that were slaughtered at Kerman slaughterhouse, Iran. The viability of protoscoleces was assessed by the eosin exclusion examination after exposure with ozone gas for 1 to 14 min in vitro and ex vivo. Results: In this study, in vitro assay showed that ozone gas at the concentration of 20 mg/L killed 85 and 100% of hydatid cyst protoscoleces after 4 and 6 min of treatment, respectively. However, in the ex vivo analysis, a longer time was needed to confirm a potent protoscolicidal activity such that ozone gas after an exposure time of 12 min, 100% of the protoscoleces were killed within the hydatid cyst. Conclusion: In conclusion, the findings of the present study showed that ozone gas at low concentrations (20 mg/L) and short times (4-6 min) might be used as a novel protoscolicidal drug for use in hydatid cyst surgery. However, more clinical surveys are required to discover the precise biological activity of ozone gas in animal and human subjects.
Keywords: in vitro